The 9-cis-epoxycarotenoid cleavage reaction is the key regulatory step of abscisic acid biosynthesis in water-stressed bean - Qin, Xiaoqiong (The National Academy of Sciences, 1999)
Abscisic acid (ABA), a cleavage product of carotenoids, is involved in stress responses in plants. A well known response of plants to water stress is accumulation of ABA, which is caused by de novo synthesis. The limiting step of ABA biosynthesis in plants is presumably the cleavage of 9-cis-epoxycarotenoids, the first committed step of ABA biosynthesis. This step generates the C(15) intermediate xanthoxin and C(25)-apocarotenoids. A cDNA, PvNCED1, was cloned from wilted bean (Phaseolus vulgaris L.) leaves. The 2,398-bp full-length PvNCED1 has an ORF of 615 aa and encodes a 68-kDa protein. The PvNCED1 protein is imported into chloroplasts, where it is associated with the thylakoids. The recombinant protein PvNCED1 catalyzes the cleavage of 9-cis-violaxanthin and 9′-cis-neoxanthin, so that the enzyme is referred to as 9-cis-epoxycarotenoid dioxygenase. When detached bean leaves were water stressed, ABA accumulation was preceded by large increases in PvNCED1 mRNA and protein levels. Conversely, rehydration of stressed leaves caused a rapid decrease in PvNCED1 mRNA, protein, and ABA levels. In bean roots, a similar correlation among PvNCED1 mRNA, protein, and ABA levels was observed. However, the ABA content was much less than in leaves, presumably because of the much smaller carotenoid precursor pool in roots than in leaves. At 7°C, PvNCED1 mRNA and ABA were slowly induced by water stress, but, at 2°C, neither accumulated. The results provide evidence that drought-induced ABA biosynthesis is regulated by the 9-cis-epoxycarotenoid cleavage reaction and that this reaction takes place in the thylakoids, where the carotenoid substrate is located.